PENGARUH MANFAAT, KEMUDAHAN DAN KEAMANAN TERHADAP MINAT PEMAKAIAN FINANCIAL TECHNOLOGY PADA APLIKASI OVO SEBAGAI DIGITAL PAYMENT (Study Kasus Mahasiswa FEB Universitas Muhammadiyah Metro) - Widi Yanto; Ery Baskor; Fitriani Fitriani (Universitas Muhammadiyah Metro, 2020)
This study aims to obtain data and find out the positive effect of benefits, convenience and security onthe interest in using financial technology in OVO applications as a digital payment study in the case of FEBstudents at the Muhammadiyah Metro University. With the technique of sampling, namely with accedentalsampling with a sampling time of 30 days to get as many as 68 samples. In this study the method used is libearyresearch and field research, namely library research, observation, interviews, correspondence, andquestionnaires. In this study the analytical tool used is multiple linear regression analysis, to determine thedependent and independent variables with the SPSS V16 For Windows program. The results of researchconducted by researchers show that there is an influence on the benefits, convenience and security of the interestin using financial technology in OVO applications as digital payments, based on the analysis results, the dataobtained is Fcount 130,280 > 2.75 and is shown by linear regression with the coefficient of determination (R2)0.859 which means that the interest in financial use in OVO applications is influenced by the benefits,convenience and safety variables of 85.9% and the remaining 14.1% is influenced by other factors outside thisstudy.